The Impact of Gamble Online the Weaking of Social Values of Teenagers (Case Study at Sidodadi Village Pekalongan District East Lampung) - Ahmad Nurndiansyah; Ikhwan Aziz Q; Suhono Suhono; Ahmad Zarnuji (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
In technology, gambling has now taken on a slightly more elite status. The way people gamble has changed due to advances in technology. Gambling no longer needs to be as secretive as it used to be. This is an illicit game that we can play just by lazing around in front of a computer connected to the internet network. The aim of this research is to characterize how adolescents' social values ​​are weakened by online gambling. Sidodadi Village, Pekalongan District, East Lampung was the research location. The method used in this research is the phenomenological method. The findings of this study indicate that the decline in teenagers' social values ​​is influenced by internet gambling. One of them is the decline in material values; For example, teenagers will run out of money if they lose in online gambling. The vital value is that teenagers pawn their possessions when they lose money in online gambling. Additionally, there is a spiritual meaning to the fact that young people use their winnings from online gambling for useless things. Keywords: Online Gambling, Social Values, Teenagers